Pengembangan Sistem Informasi Pada Local E-Govervenance Untuk Peningkatan Kinerja Pelayanan Warga - Yutanto, Hariadi; Ilham, Romi; Salma, Kautsar Riza; Effendi, Yusuf (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
The problems that often arise in the neighborhood of Neighborhood Unit (RT) and Rukun Warga (RW) are the distribution of information on citizen activities, administration, transparent financial management, and management of citizen databases as an effort to improve services and information facilities for residents. The purpose of this study is to support the government in implementing e-Government-based government systems, by developing Good Local Governance. The specific target of innovation to be achieved is the development of innovation in the form of a web-based Citizen Information System (SiWarga) application at the RT / RW level. The method used in this study uses the System Development Life Cycle (SDLC Waterfall) method, starting from the first is analyzing the needs by conducting a survey and the feasibility of developing the system, second is to make a detailed list according to system requirements specifications, third is to design the system by creating workflow designs and programming design, the fourth is the development of information systems with coding, the fifth is system testing, the sixth is the implementation and maintenance of the system